Media, Ecology and Technology: Holistic Approach - Elango, Elango (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
Today we are in the Hyperreal World in the Post Modern Era, bound to meet media, ecology and Technology. We need Mother Earth to have Ecological balance for Human and living organisms' Survival. To Every Individual to have a Holistic Life, we need eco-friendly Technology and an excellent environment to lead a pleasant, harmonious life. Ecology are the scientific study of the relationships between living organisms and their physical and biology environments. It encompasses the study of the distribution and abundance of living things, the interactions between organisms, and the relationships between organisms and their physical and chemical surroundings. The ecology perspective is a way of looking at the world that emphasizes the interconnectedness and interdependence of all living things and their environments. To have an Ecological Perspective, we need technological development and support to handle the issues and problems from a social perspective. This research study analyses the role of ecology, Technology and media and their interconnectedness in the holistic approach. The researcher conducted in-depth interviews with media specialists and Teachers in Environmental Studies and gathered valuable insights on media, ecology and Technology and their connectivity in bringing a holistic approach. Media and ecology today give a Hyperreal experience for the audience with the advancement in Technology. Media Creates a Hyperreal Environment in day-to-day life for the social well-being of humans and living organisms and awareness of environmental problems created. Environmental Activists use media platforms for their activist activities.